SIMULATION AND EXPERIMENT STUDY ON THE EFFECT OF COATING ON LOCKING TORQUE OF SELF-LOCKING BOLTS (MT) - LIU BenLing; WU BaoQuan; ZHANG Tao; LIN ZhongLiang; CHAI JinBao; WANG HongFei; BAI QingShun (Jixie qiangdu)
In order to solve the problem of bolt loosening and failure, based on self-developed aviation self-locking bolts, the influence of locking coating on locking performance of self-locking bolts was studied, and the locking effect of bolts with molybdenum disulfide（MoS2）, nylon 11（PA11） and polyvinyl chloride（PVC） coating materials was explored. Bolt connection locking mechanism are analyzed in this paper, by using the method of finite element simulation analysis and experimental verification, the air with the self-locking bolt lock the simulation and experimental research of the coating material selection, the mathematical model of the thread contour complete accurate set finite element meshing, boundary conditions, load simulation, experimental verification and test bench.The results show that the average locking torque of MoS2, PA11 and PVC is 1.06 N·m, 1.95 N·m and 2.18 N·m respectively in the finite element simulation. When PA11 is used as the coating, it is closer to the requirement that the maximum locking torque is less than or equal to 2.05 N·m in American standard IFI524. The bench test verifies that the average locking torque of the locking bolt with PA11 coating material is 1.82 N·m. Compared with the value of simulation analysis, it is within a reasonable fluctuation range, and PA11 as the coating material can meet the actual production requirements.